Ireland's gramophones : material culture, memory, and trauma in Irish modernism - Cammack, Zan (Clemson University Press, 2021)
"Ireland's Gramophones examines the perpetual presence of the gramophone in literature of Irish modernism: the same period in which gramophonic technology grew to cultural prominence. The book argues that the gramophone, as object and instrument, embodies accounts of a culture frequently traumatized through violence and disruption"--